1997
DOI: 10.1364/ol.22.000233
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diodes as measurement devices for femtosecond laser pulses

Abstract: We present results showing that, when it is used as a photodetector, a light-emitting diode (LED) has a power-dependent response that can be used for sensitive detection and characterization of picosecond and femtosecond laser pulses. A characterization of a typical LED is presented at 800 nm, and we demonstrate how this effect can be used to construct an extremely compact novel autocorrelator based on a Wollaston prism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(48 citation statements)
references
References 6 publications
1
43
0
1
Order By: Relevance
“…We have also shown that the interferometric autocorrelation of a sub-5-fs compressed pulse, similar to the one depicted in Fig. 14, can be obtained by measuring the two-photon-induced photocurrent [128,129] in a GaP photodiode [130].…”
Section: Note Addedmentioning
confidence: 68%
“…We have also shown that the interferometric autocorrelation of a sub-5-fs compressed pulse, similar to the one depicted in Fig. 14, can be obtained by measuring the two-photon-induced photocurrent [128,129] in a GaP photodiode [130].…”
Section: Note Addedmentioning
confidence: 68%
“…TPA in photodiodes [9], [18] and AlGaAs lightemitting diodes (LEDs) [19] for autocorrelation measurement of picosecond and femtosecond laser pulses has been previously demonstrated. Also, waveguide TPA in commercial laser diodes has also been used to fully characterize picosecond pulses in the temporal and phase domain [20].…”
Section: A Principle Of Tpa Autocorrrelationmentioning
confidence: 99%
“…Phase mismatch, in particular, can lead to a spectral-filtering effect to make a measured autocorrelation function significantly distorted. Several groups have demonstrated that TPA or 3PA based processes can be effective for pulse diagnostics in the femtosecond and picosecond time range with photodiodes using Si [2,3], GaAsP [2,[4][5][6][7], InGaAs [8], SiC [9,10], ZnSSe [11], GaN [12], light-emitting diodes using AlGaAs [13], laser diodes using GaAsP [3], GaAs/AlGaAs [14], GaN [15] and photocathodes using CsI and CuI PMTs [16] in autocorrelator schemes. Other semiconductor waveguides and microcavity structure devices were also developed [17][18][19].…”
Section: Introductionmentioning
confidence: 99%